Long term fMRI adaptation depends on adapter response in face-selective cortex - Daphne Stam (Nature Portfolio, 2021)
In order to examine underlying mechanisms of repetition suppression, Stam et al conducted an fMRI study in which participants were presented with face and house stimuli followed by an immediate and 48 h-delayed memory task. Their data demonstrated that adapter-related and familiarity account modelling are more likely to be more accurate for visual memory than previous predictive coding models.